Observations on the sustainability of biodiversity through seed dispersal in a microecosystem. (3rd July 2021) - Yurumezoglu, Kemal; Oztas Cin, Merve
Abstract: In this study, an extracurricular observation module is suggested for the purpose of observing the sustainability of biodiversity based on gathering evidence regarding different seed dispersal processes in the natural environment. These observations were made during the period of the Covid-19 pandemic, a time when human activity inflicted a minimum level of damage. The location of the observations was a microecosystem discovered on an urban college campus. Observations were made of four different types of seeds (palm, mulberry, linden and laurel) inside this ecosystem as well as of the way they were being carried via three different means (gravity, wind and the birds). The methods of how evidence of these seed-carrying processes was collected are presented here. A systematic and sequential observational technique in three steps is suggested to facilitate understanding the germination, growth and development processes of the different seeds in the microecosystem explored. We propose on the basis of this module that anyone can discover a microecosystem in their immediate environment and that with systematic observations can develop the skills needed to gather evidence on the ways seeds are disseminated and how plants grow. The entire construct of this study has been structured to support this claim.